Al-Quran Hadith Learning Design in Facing the Era 5.0 - Hendra, Ritman; Rahman, Yenni; Humaeroh, Iis; Niimmasubhani, Niimmasubhani; Alfiyanto, Afif (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
Al-Quran Hadith is one of the subjects in the Islamic Religious Education (PAI) and Arabic language. This subject is important to learn without reducing the importance of other subjects that are still in the same family or other general subjects being taught. This article aims to provide strategies for finding appropriate and relevant patterns related to the development of science and technology; times have changed towards the era of society 5.0. Changing is a strategy used by the tutors of Al-Quran Hadith subjects while continuing to update their knowledge to deal with changes, which changes cannot be restrained and inhibited. So that students have the stimulation to study the Al-Quran Hadith to encourage them to be individuals who give benefits to themselves, their families and society. Many cases in this country can be minimized through students' understanding of the Al-Qur’an and Hadith. This research was library research and used a descriptive qualitative approach. The data were collected through various articles and relevant books. A descriptive analysis was carried out and conclusions were made. The result of this article showed a strategy that must be owned by educators was adapting to the times they are facing, especially the subjects of the Al-Quran and Hadith as the main guidance for Muslims